The Impact of Endotracheal Intubation on Hemodynamic Parameters and Associated Respiratory Complications in Hospitalized Patients in Intensive Care Unit at Western Libya - Wafa Abdulhafid Said; Faraj Khamees Saqar; Hadeel Mohammed Al-Faqi; Khulood Mohammed Al-Mizughi; Mawdah Muammar Al-Fard; Najwa Muftah Juha; Retaj Mohammed Ahmed; Retaj Mukhtar Farhat (African Journal of Advanced Pure and Applied Sciences, 2025)
Endotracheal intubation is essential for managing respiratory failure and facilitating general anesthesia. While it provides airway protection and ventilation, it can also cause significant hemodynamic changes and respiratory complications. This study examines the effects of endotracheal intubation on hemodynamic parameters—heart rate, blood pressure, and oxygen saturation—among hospitalized patients in Western Libya. The study was conducted in various hospitals between February 19 and June 9, 2024, included 80 patients aged 18 to 75. Data were collected using a structured questionnaire, focusing on factors like age, type of surgery, and pre-operative medications. Hemodynamic changes were monitored in the first three minutes post-intubation. Results showed that 67.5% of participants were female. At 1 minute post-intubation, 41.3% experienced bradycardia, while blood pressure remained stable in 75% of patients. Oxygen saturation levels were also stable, indicating effective respiratory management. Notable respiratory complications included one case of apnea, four cases of bronchospasm, and one case of hypoxia. The study highlights that intubation can induce hemodynamic responses due to vagal stimulation and sympathetic activation. Despite stable hemodynamic parameters, the occurrence of bronchospasm emphasizes the need for effective airway management. Future research should focus on larger, more diverse populations and compare different intubation techniques to enhance clinical practices. Continuous refinement of intubation strategies is crucial for improving patient outcomes and ensuring safety during surgical procedures.